2024
DOI: 10.1039/d3nr04298g
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation of synergistically boosting the anchoring and electrochemical performance of lithiophilic/sulfiphilic transition metal carbides for lithium–sulfur batteries

Mingyang Wang,
Jianjun Mao,
Yudong Pang
et al.

Abstract: Synergistically boosting the anchoring and electrochemical performance of lithiophilic/sulfiphilic transition metal carbide (001) surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 66 publications
(81 reference statements)
0
1
0
Order By: Relevance
“…We also summarized the different types of metal phosphides and their performances on the battery in Table 1. 104–108 It has been reported that lithium–sulfur button cells with metal phosphides have good electrochemical properties under different rates and have good cycle stability in soft package batteries. 109–111 The clearly delineated design principles and comprehensive exploration of catalytic mechanisms related to phosphides have offered significant insights for constructing excellent efficiency and long-lasting Li–S batteries.…”
Section: Discussionmentioning
confidence: 99%
“…We also summarized the different types of metal phosphides and their performances on the battery in Table 1. 104–108 It has been reported that lithium–sulfur button cells with metal phosphides have good electrochemical properties under different rates and have good cycle stability in soft package batteries. 109–111 The clearly delineated design principles and comprehensive exploration of catalytic mechanisms related to phosphides have offered significant insights for constructing excellent efficiency and long-lasting Li–S batteries.…”
Section: Discussionmentioning
confidence: 99%